Education in action: evaluating kids concussion infographics. Issue 11 (25th May 2017) - Provvidenza, Christine; Carmichael, Jason; Reed, Nick
Abstract : Objective: To assess the impact of infographics on enhancing concussion knowledge and their effectiveness as a knowledge translation (KT) strategy. Design: Prospective, post-survey design to assess a KT strategy. Setting: Community and hospital based education events. Participants: Individuals across various stakeholder groups were invited to provide feedback on six infographics. Data (N=106) was collected from youth (52%) and adults (48%), representing five stakeholder groups: athletes, students, teachers, healthcare trainees and healthcare professionals. Intervention: Six infographics were created to provide salient information about concussion for a multi-stakeholder audience. Outcome measures: A survey was designed to gather information about the value and utility of the infographics as a KT strategy and to determine additional knowledge needs. Main results: Ninety percent of participants identified that the infographics met their knowledge needs, and 84% of participants indicated that the infographics gave them new knowledge related to sleep, myths and facts, and signs and symptoms. Participants indicated that they intend to use the infographics to build knowledge (91%), educate others (52%), and cope with concussion (26%). Feedback provided about the infographic format was positive, and suggestions for future topics were offered. Conclusions: Infographics are a potentially effective KT strategy that meets knowledge needs and appeals to many different audiences. Participants identified that they want to learn more about areas including concussion recovery and management. Data collection is ongoing and continues to inform the value of infographics as a KT strategy. This study is part of a broader education initiative to optimise paediatric concussion knowledge. Competing interests: None.